Corrosion Inhibition Effect of Centella asiatica (Vallarai) on Mild Steel in Hydrochloric Acid - Shyamala, M.; Arulanantham, A. (Asian Journal of Chemistry, 2010)
Corrosion of oil and gas well equipment during acidization process causes severe problem in oil and gas well industries. This problem can be prevented to a maximum extent by the application of corrosion inhibitors. Present work involves the study of aqueous extract of Centella asiatica as corrosion inhibitor on mild steel in 1 N hydrochloric acid and has been investigated by weight loss method, gasometric method, potentiodynamic polarization method and AC impedance method. Centella asiatica yields maximum inhibition efficiency of 85-86 % in presence of an optimum concentration of 10 % v/v of the extract. The inhibition efficiency was found to vary with its concentration, temperature, immersion time. Potentiodynamic polarization studies show that Centella asiatica is a mixed type inhibitor. It inhibits mild steel corrosion by blocking the active sites of metal. Results obtained in non electrochemical methods (weight loss method and gasometric method) have good agreement with the electrochemical methods (potentiodynamic polarization method and impedance method). The adsorption of Centella asiatica follows Langmuir adsorption isotherm. The inhibition action is due to the presence of Asiaticoside, a triterpene glycoside present in the leaves of Centella asiatica.